Development of automated fault location software for distribution network - Mokhlis, Hazlie; Khalid, A.R.; Li, H.Y. (IEEE, 2006)
This paper presents on an ongoing development of automated fault location software for distribution network. The proposed method of the software is able to identify the most possible faulty section based on voltage sags feature i.e. magnitude and phase shift. The actual voltage sags caused by fault is compares with simulated voltage sags stored in a database. The matching will give all possible faulty sections that have been stored in the database. The software is developed by integrating various software modules. The module will be developed into a component type using Component Based Development (CBD) approach. By developing the software from component, replacement or modification can be done to any of the module without affecting the whole software. The test results of the proposed method show satisfactory. Future works in order to improve the software and method are also discussed in this paper.